Edible bird's nest (EBN) is a potential natural product against influenza virus infection - Akmal, M. N.; Abdul Razak, Intan Shameha; Md. Ajat, Mohd Mokrish; Ideris, Aini (Veterinary Association Malaysia, 2017)
Edible bird’s nest (EBN) is an emergent industry in Malaysia. In 2016, EBN worth RM 1.2 billion with the total production of 228-tonne metrics. EBN is salivary secretion of swiftlets (Aerodramus spp.) that contained various nutritive values. Back in Tang Dynasty, it had been recognized as a natural product with broad medicinal effects. Recently, various scientific studies have been done to elucidate the medicinal properties of this precious food. For the past 10 years, antiviral effects of EBN had been explained via in-vitro and in-vivo well-designed researches, in which generally EBN is exerting a good alternative food for prophylactic and therapeutic agent against Influenza A virus infection in the laboratory setting. The limited study had been done to identify the bioactive ingredient of EBN that have antiviral properties. Nevertheless, based on the previous nutritional studies, some contents of EBN have been hypothesised to serve as an antiviral agent, and comprehensive study is required to explicate those claimed. The aim of this paper is to review on the recent discovery pertaining to the potential antiviral effect of EBN in the cell culture and animal model studies.